Assessment of community-based intervention approaches to improve the health and welfare of working donkeys in selected areas of Sidama region, Southern Ethiopia - Yalew, Aweke; Darge, Daniel; Melake, Berhanu Mekibib (Frontiers in Veterinary Science, 2024)
Background Although efforts have been made by certain non-governmental organizations, like the Donkey Sanctuary, SPANA (Society for the Protection of Animals Abroad), and Brooke Ethiopia, to change the attitudes and practices of donkey owners toward improving the health and welfare of working donkeys, their impact has not been assessed so far. A cross-sectional study was conducted to assess and compare donkeys’ health and welfare problems in community-based intervention areas versus non-intervention areas in selected districts of Sidama regional state, Southern Ethiopia. Methods For the animal-based welfare assessments, 200 donkeys each were selected and included from intervention and non-intervention areas. The selected donkeys were then assessed for their welfare and health status using five important parameters, namely, body condition score, presence and severity of wounds, behavior, presence and severity of lameness, and presence of other signs of illness/diseases. Results The prevalence and severity of lameness and wounds on donkeys managed in non-intervention areas were higher than those observed in community-based intervention areas. The prevalence of lameness in the non-intervention areas (25.5%) was over two times higher than the prevalence in the intervention areas (12%). Likewise, over 37% of the donkeys in the non-intervention areas were wounded, of which 64% were suffering moderate to severe wounds. Moreover, donkeys in the intervention areas had better body condition and were alert and friendly upon human approach. There was a statistically significant difference (p < 0.01) between the intervention and non-intervention areas in all the considered parameters, namely, the presence of lameness, wound, body condition score, demeanor, and response to approach. Conclusion and recommendations Based on this study’s findings, the community-based intervention approach was found to improve the health and welfare of working donkeys. Therefore, comprehensive and continuous equine health and welfare promotion through community-based intervention approaches should be designed and implemented to improve the welfare of working equines in the country.